ANALISIS SELISIH PAJAK PERTAMBAHAN NILAI (PPN) MASUKAN DAN PPN KELUARAN DALAM PROSES REKONSILIASI PADA PT. XYZ - Maulidatul Salsabila; Wasti Reviandani (MANAJEMEN DEWANTARA, 2026)
The purpose of this research is to identify and analyze in depth the causes of discrepancies between input VAT and output VAT during the tax reconciliation process at PT.XYZ. This study employs a descriptive qualitative research method. Data were collected through observation and interviews. The results indicate that discrepancies between input and output VAT occur due to several factors, including delays in receiving input VAT invoices, errors in transaction recording, and the existence of VAT invoices that have not yet been verified in the e-Faktur system